Assessing Perceptions and Adaptation Responses to Climate Change among Small-Scale Fishery on the Northern Coastal of Bengkulu, Indonesia - Gita Mulyasari; Agung Trisusilo; Nola Windirah; Ira Nurhayati Djarot; Agusta Samodra Putra (The Scientific World Journal)
Small-scale fisheries are facing significant challenges from climate change. Fishers feel the impact of climate change, which forces them to adapt. We, therefore, analyzed local climatic changes, fishers’ perceptions regarding climate change and its impacts, adaptation responses, and determinants. Three decades of meteorological data were analyzed (1985–2020). A total of 300 fishermen were selected using quota sampling and interviewed using a structured questionnaire. Data were analyzed using the descriptive and binary logit regression models to explain the determinants of adaptation responses. The findings indicate that fishers’ perceptions of climatic changes align with historical climatic data. Typologies of adaptation responses used in the study showed that time fishing adjustment was the most widely used adaptation option by fishermen. For this reason, fishermen are very active in looking for information about climate change to help them find the right time to go to sea and reduce the risk of climate change. Analysis using the binary logit regression model showed that fishing income, boat power, and climate change perceptions were the significant (p<0.1) factors significantly influencing adaptation responses. Therefore, to strengthen the adaptation responses in small-scale fisheries, fishers’ perceptions should be considered.